Pengembangan Sistem Point Of Sale Berbasis User Centered Design - Raihan, Muhammad Rafi; Hidayahtullah, Deny (STMIK Budi Darma, 2022)
UD Tebar Gembira is an UMKM engaged in the sale of herbal drinks. The obstacle faced by UD Tebar Gembira during its business activities is the absence of a POS (Point of Sale) system that functions as a tool in recording purchase transaction data and complete inventory of goods. The methodology applied in this research is the User Centered Design (UCD) method which is an applied method that aims to solve practical problems in the modern world. The result of this research is a web-based POS (Point of Sale) application. The implementation of the research has had many positive impacts where the owner of the Tebar Gembira trading business as a user feels it is easy to refill the stock of goods because they can directly monitor the amount of inventory that has been recorded in the system.